Chipless RFID tag design, simulation and measurement with data processing method - Liu, Lingyu. (2013)
Chipless (Radio Frequency Identification) RFID tag is low cost and can be a replacement of barcode in the future. One method is spectral signature based chipless RFID tag design which enables the tag to be fully printable, large data capacity and low cost compare with other chipless RFID tag design techniques.